Decentralization, Public Services and Neglected Children in Mataram City, West Nusa Tenggara - Chairun Nasirin; Andries Lionardo (Research Horizon, 2021)
One of the problems that are now the concern of the local government in Mataram is the phenomenon of neglected children, where the child is the hope of the nation that has a strategic role in enhancing the continuity of the nation's existence in the future. The main issues of neglected children in Mataram are rooted in the problem of poverty, so the handling should touch on the root of the problems. Regarding the matter, the government is arranging a program for the administration and empowerment of abandoned children. The Program is a neglected children's social welfare protection with other additional activities. In this context, the government uses decentralization. Decentralization will encourage people towards a self-propelled way by enabling social capital to solve the problems they are facing. With a proper procedure in addressing social issues that have been internalized, a neglected children's completion mechanism will be more productive and more efficient. While economically, decentralization in the belief can prevent exploitation in the central government of the region and can generate the innovation of society and encourage the motivation of the community to be more productive.